The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1515/fascmath-2015-0002
|View full text |Cite
|
Sign up to set email alerts
|

Distributive Pseudo Be-Algebras

Abstract: In this paper, we introduce the notion of distributive pseudo BE-algebra and show that the related relation defined on this structure is transitive and prove that every pseudo upper set is a pseudo filter. Also, the pseudo filter generated by a set is define and show that the set of all pseudo filters is distributive complete lattice but it is not complemented. the notion of prime and irreducible subset and prove that every irreducible subset is prime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 4 publications
0
16
0
Order By: Relevance
“…Remark 2.3: If X is a pseudo BE-algebra satisfying x * y = x y, for all x, y ∈ X, then X is a BE-algebra. [2]) In a pseudo BE-algebra X, the following statements hold:…”
Section: Preliminariesmentioning
confidence: 99%
See 3 more Smart Citations
“…Remark 2.3: If X is a pseudo BE-algebra satisfying x * y = x y, for all x, y ∈ X, then X is a BE-algebra. [2]) In a pseudo BE-algebra X, the following statements hold:…”
Section: Preliminariesmentioning
confidence: 99%
“…Definition 2.5: [2] A pseudo BE-algebra X is said to be distributive if it satisfies in the following condition:…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…Rezaei et al introduced the notion of distributive pseudo BE-algebras and normal pseudo filters and proved some basic properties. They showed that in distributive pseudo BE-algebras normal pseudo filters and pseudo filters coincide [4]. L.C.…”
Section: Introductionmentioning
confidence: 99%